The Effectiveness of POKJA (Javanese Script Posters) to Introduce Java Script - Fardani, Much Arsyad (Asian Journal of Applied Education (AJAE), 2023)
POKJA media is learning media in the form of posters that contain reading and writing exercises in Javanese script which are presented with pictures accompanied by decorations so that they can attract students' attention and make it easier for students to understand the material while studying. This study aims to determine the effectiveness of POKJA media (Javanese Script Posters) in increasing the introduction of Javanese script in class III elementary school students. The research method used in this study was an experimental method using a saturated sample technique using third-grade students at SD 1 Peganjaran and SD 2 Peganjaran with a total of 20 students. The data collection instrument uses evaluation test questions which are carried out after using the media. The results obtained from this study were that the POKJA learning media (Javanese script posters) had a major impact on increasing student scores as seen from the results of the evaluation test scores carried out. Testing the effectiveness of the use of instructional media through the implementation of evaluation tests obtained an average score of 81.25 with KKM > 70 by students in two research education injections, so that students were declared complete. Thus, the POKJA media (Javanese script posters) is effective as a medium for introducing Javanese script to third-grade elementary school students.